2017
DOI: 10.1039/c7ce00263g
|View full text |Cite
|
Sign up to set email alerts
|

Selective binding in different adsorption sites of a 2D covalent organic framework

Abstract: This study shows that surface-supported two-dimensional (2D) porous covalent organic frameworks (COFs) can selectively bind different molecules at specific sites via different types of interactions. Scanning tunneling microscopy (STM) images collected at the liquid/solid interface reveal the adsorption of 1,2,4-trichlorobenzene (TCB) in the hexagonal pore of a COF-1 template. A well-defined loop boundary formed by a chain of pentagonal and heptagonal pores allowed the investigation of the effect of pore shape … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 41 publications
6
20
0
Order By: Relevance
“…The adsorption of solvent molecules in the host lattice can be used to control the adsorbed site of guest molecules. 111 Fullerenes adsorb on the top-site of COF-1 (Fig. 3j) when both C 60 and TCB are present at the TCB/HOPG interface since the pore-site is blocked by the adsorption of TCB molecule.…”
Section: Selective Binding Of Molecules In a Host-guest Structurementioning
confidence: 99%
“…The adsorption of solvent molecules in the host lattice can be used to control the adsorbed site of guest molecules. 111 Fullerenes adsorb on the top-site of COF-1 (Fig. 3j) when both C 60 and TCB are present at the TCB/HOPG interface since the pore-site is blocked by the adsorption of TCB molecule.…”
Section: Selective Binding Of Molecules In a Host-guest Structurementioning
confidence: 99%
“…Our results suggest that the confinement of reactions on a crystalline substrate may be an efficient way to select the desired polymorph. In future investigations host-guest chemistry for ST 41,[44][45][46] and the elucidation of the electronic properties 26,27 in such fractal confinements may reveal intriguing phenomena.…”
mentioning
confidence: 99%
“…These results reveal the stepwise breakdown in ordering caused by the anisotropy and suggest that using a surface‐confined template to anchor the initial layer of LC molecules could be a modular and potentially broadly applicable approach to organizing molecular mesogens to form new LCs. Moreover, our previous work has shown that solvents can be used to select the adsorption sites of guest molecules in similar systems . Even though several C 70 mesophases were observed in heptanoic acid, exploiting a different solvent molecule, such as 1,2,4‐trichlorobenzene, may selectively form a single phase.…”
Section: Discussionmentioning
confidence: 99%
“…Small 2019, 15,1903294 of guest molecules in similar systems. [23,51] Even though several C 70 mesophases were observed in heptanoic acid, exploiting a different solvent molecule, such as 1,2,4-trichlorobenzene, may selectively form a single phase. The combination of template, solvent, and anisotropy of building blocks implies an effective approach to controlling molecular packing from 2D to 3D, which has the potential to provide structural control over properties in device-relevant films.…”
Section: Wwwsmall-journalcommentioning
confidence: 99%